Chemistry : course companion - Neuss, Geoffrey (New York : Oxford University Press, 2007)
A resource for students participating in the International Baccalaureate Diploma Programme that provides content and activities which enhance knowledge and encourage thinking and reflection about topics in chemistry.
"In cooperation with IB."
Includes index.
Adult
Keywords: Chemistry -- Study and teaching (Secondary); International baccalaureate -- Study guides; Chemistry -- Study and teaching; IB Programme -- Chemistry; International baccalaureate -- Study guides